Deep brain stimulation in posterior subthalamic area for Holmes tremor: Case reports with review of the literature - Kamo, Hikaru; Oyama, Genko; Ito, Masanobu; Iwamuro, Hirokazu; Umemura, Atsushi; Hattori, Nobutaka (Frontiers in Neurology, 2023)
Background Holmes tremor (HT) is a refractory tremor associated with cortico-basal ganglia loops and cerebellothalamic tract abnormalities. Various drug treatments have been attempted; however, no treatment method has yet been established. Historically, thalamic deep brain stimulation (DBS) has been performed in medically refractory cases. Recently, the posterior subthalamic area (PSA) has been used for HT. Here, we report cases of HT and review the effectiveness and safety of PSA-DBS for HT. Cases We conducted a retrospective chart review of two patients with HT who underwent PSA-DBS. Improvement in tremors was observed 1 year after surgery without apparent complications. Literature review We identified 12 patients who underwent PSA-DBS for HT, including our cases. In six patients, PSA was targeted alone; for the rest, the ventralis intermediate nucleus (Vim) of the thalamus and PSA were simultaneously targeted. The Fahn–Tolosa–Marin Tremor Rating Scale improvement rates were 56.8% (range, 33.9–82.1%; n = 6) and 77.8% (range, 42.6–100%; n = 5) for the PSA-DBS and PSA+Vim-DBS, respectively. Conclusion Reasonable improvements in HT were observed after PSA-DBS. PSA might be an appropriate target for improving the symptoms of HT. Long-term observations, accumulation of cases, and randomized studies are required in future.